2011
DOI: 10.1515/libr.2011.015
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Intelligence Practices and Firm Performance

Abstract: This study examines the level of competitive intelligence practices undertaken by Malaysian publiclisted companies, and the relationship between competitive intelligence and firm performance. Data was collected from 123 companies across various industry categories. The study finds that competitive intelligence has been practiced at an early stage and in a moderate level among Malaysian companies. The top three intelligence sectors rated by the sampled companies are customers, competitors and the economy. Compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…However, sustainable excellent performance will not occur if there is a misalignment between a firm's competitive strategies and actual customer life cycle requirements. In addition, globalization has caused competition to be a constant concern of organizations, by increasing the need for continuous evaluation of the competitive environment and the information coming out of it (McKenzie, van Winkelen, and Grewal, 2011;Sharma, and Dijaw, 2011;Yap, and Rashid, 2011). The insurance sector is currently in a state of some uncertainty and companies are increasingly conscious of the need to maintain a competitive edge over their commercial rivals while at the same time getting maximum benefits from in-house resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, sustainable excellent performance will not occur if there is a misalignment between a firm's competitive strategies and actual customer life cycle requirements. In addition, globalization has caused competition to be a constant concern of organizations, by increasing the need for continuous evaluation of the competitive environment and the information coming out of it (McKenzie, van Winkelen, and Grewal, 2011;Sharma, and Dijaw, 2011;Yap, and Rashid, 2011). The insurance sector is currently in a state of some uncertainty and companies are increasingly conscious of the need to maintain a competitive edge over their commercial rivals while at the same time getting maximum benefits from in-house resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of an emerging economy, a study on Malaysian public listed companies showed that the relationship between competitive intelligence and firm performance is positive (Yap and Md Zabid, 2011). Moreover, the performance of firms with a formal competitive intelligence practices outweigh the performance of those firms without a formal competitive intelligence practice.…”
Section: Market Intelligence Practices and Firm Performancementioning
confidence: 99%
“…formally acquire and utilize market information and whether such practices did affect their performance positively. Most prior studies on market information acquisition and utilization are conducted on large and established firms (Adidam et al, 2012;Jaworski and Kohli, 1993;Matsuno and Mentzer, 2000;Yap and Md Zabid, 2011), related to new ventures success (Song et al, 2009, or new product performance (Droge et al, 2008). Apart from the evidence provided by Keh et al (2007), there is a limited amount of empirical evidence on formal market information processes among small-and medium-sized firms.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, another survey confirms the existence of a close link, albeit not a causal relationship, between CI practices and business performance, to the extent that companies that carry out many activities of this type evidence a greater capacity for strategic decision making that leads to better company performance. Companies that have created management sections or units for CI activities tend to be more profitable organizations than those that have not done so, and activities they develop may help company management to take decisions regarding expansion to develop new products and/or services (Yap & Rashid, ).…”
Section: The Introduction Of Competitive Intelligence Practices In Smmentioning
confidence: 99%